The Influence of Taste, Price and Word of Mouth on Purchasing Decisions at Anyeong Risol Business in Pasuruan, East Java - Diah Zumarotul Islamiyah; Rini Rahayu Kurniati; Dadang Krisdianto (CV. Proaksara Global Transeduka, 2024)
This study investigates how word of mouth, price, and taste influence purchasing decisions at Anyeong Risol company in Pasuruan, East Java. A quantitative method of correlation was used in this research. Data was collected through Likert scale questionnaires. The sample consisted of one hundred customers of Anyeong Risol company in Pasuruan, East Java. Hypothesis testing and classical assumptions were also used to examine the data. The research results indicate that taste influences customers' purchasing decisions and the first hypothesis was accepted. The second hypothesis was accepted because price and purchasing decisions have a significant positive effect. There is a positive word of mouth effect on purchasing decisions. Taste, price, and feedback in Anyeong Risol business in Pasuruan, East Java, all influence purchasing decisions. This research can help Anyeong Risol business in Pakukerto Village, Sukorejo District, Pasuruan Regency to maintain existing factors and encourage customers to become loyal customers.